2020
DOI: 10.1021/acs.jpcc.0c03871
|View full text |Cite
|
Sign up to set email alerts
|

Shapes, Plasmonic Properties, and Reactivity of Magnesium Nanoparticles

Abstract: Localized surface plasmon resonances have attracted much attention due to their ability to enhance light–matter interactions and manipulate light at the subwavelength level. Recently, alternatives to the rare and expensive noble metals Ag and Au have been sought for more sustainable and large-scale plasmonic utilization. Mg supports plasmon resonances, is one of the most abundant elements in earth’s crust, and is fully biocompatible, making it an attractive framework for plasmonics. This feature article first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
89
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 119 publications
0
89
0
Order By: Relevance
“…With a strong plasmonic response in the UV range, Mg nanoclusters could potentially complement conventional plasmonic materials, which typically absorb in the visible or near UV range. [1][2][3][4]32,35 In order to further characterize the plasmonic behaviour of Mg nanoclusters, we report the homogeneous linewidth (Γ) and lifetime (T 2 ) associated with its plasmonic excitation. The homogeneous linewidth can be calculated by fitting the time-dependent dipole moment response (µ(t)) when the nanostructure is illuminated with a sinusoidal time-dependent electric field as an external perturbation.…”
Section: Comparison Of Plasmonic Response Of Mg and Ag Nanoclustersmentioning
confidence: 99%
See 4 more Smart Citations
“…With a strong plasmonic response in the UV range, Mg nanoclusters could potentially complement conventional plasmonic materials, which typically absorb in the visible or near UV range. [1][2][3][4]32,35 In order to further characterize the plasmonic behaviour of Mg nanoclusters, we report the homogeneous linewidth (Γ) and lifetime (T 2 ) associated with its plasmonic excitation. The homogeneous linewidth can be calculated by fitting the time-dependent dipole moment response (µ(t)) when the nanostructure is illuminated with a sinusoidal time-dependent electric field as an external perturbation.…”
Section: Comparison Of Plasmonic Response Of Mg and Ag Nanoclustersmentioning
confidence: 99%
“…38,40,41,43 This property has been discussed in the literature in the context of hydrogen storage. 32,34,35,39 In the following, we will interpret the predicted optical properties of Mg nanoclusters in the context of plasmonic enhancement of hydrogen dissociative adsorption and associative desorption (hydrogen evolution). In the previous sections, we have shown that LSPR excitation of Mg nanoclusters produces hot electrons with energies of up to 4 eV.…”
Section: Plasmonic Enhancement Of Hydrogen Dissociation On Mg Nanoclustersmentioning
confidence: 99%
See 3 more Smart Citations